Systematic Review of Shariah Stock Investments Globally: A Decade of Progress and Trends Analysis - Sahara, Safira; Apriantoro, Muhamad Subhi; Rosyadhi, Rozi Irfan (TAWAZUN: Journal of Sharia Economic Law, 2024)
This study aims to explore the global development of Sharia-compliant stock investment by examining renowned international journal publications. This study employs a methodical literature review approach to look for papers using the term “Islamic Stocks” utilizing the Scopus aggregator. The author reviewed 71 research publications on Islamic shares published between 2014 to 2023. Based on these findings, the diversification of Islamic stocks provides notable benefits as it considers economic groupings ranging from industrialized to emerging nations. Islamic investment principles and mood are significant factors in the dynamics of the financial market. The Islamic stock market is often less dangerous during times of extreme events. Despite the COVID-19 pandemic affecting the stability of the Sharia stock index, some stocks have demonstrated their ability to withstand changes in investor state of mind. Essentially, this literature aims to provide basic guidance for decision-makers in investing and risk management in Islamic financial markets. It covers topics such as the potential of Islamic markets, risk, exposure, and interactions with external factors.